Insights into the Social Behavior of Surface and Cave-Dwelling Fish (Poecilia mexicana) in Light and Darkness through the Use of a Biomimetic Robot - Bierbach, David; Lukas, Juliane; Bergmann, Anja; Elsner, Kristiane; Höhne, Leander; Weber, Christiane; Weimar, Nils; Arias-Rodriguez, Lenin; Mönck, Hauke J.; Nguyen, Hai; Romanczuk, Pawel; Landgraf, Tim; et al. (Frontiers in Robotics and AI, 2018)
Biomimetic Robots (BRs) are becoming more common in behavioral research and, if they are accepted as conspecifics, allow for new forms of experimental manipulations of social interactions. Nevertheless, it is often not clear which cues emanating from a BR are actually used as communicative signals and how species or populations with different sensory make-ups react to specific types of BRs. We herein present results from experiments using two populations of livebearing fishes that differ in their sensory capabilities. In the South of Mexico, surface-dwelling mollies (Poecilia mexicana) successfully invaded caves and adapted to dark conditions. While almost without pigment, these cave mollies possess smaller but still functional eyes. Although previous studies found cave mollies to show reduced shoaling preferences with conspecifics in light compared to surface mollies, it is assumed that they possess specialized adaptations to maintain some kind of sociality also in their dark habitats. By testing surface and cave-dwelling mollies with RoboFish, a BR made for use in laboratory experiments with guppies and sticklebacks, we asked to what extent visual and non-visual cues play a role in their social behavior. Both cave and surface-dwelling mollies followed the biomimetic robot as well as a live companion when tested in light. However, when tested in darkness, only surface-dwelling fish were attracted by a live conspecific while cave fish were not. Neither cave nor surface-dwelling mollies were attracted to RoboFish in darkness. This is the first study to use biomimetic robots for the investigation of social behavior in mollies and to compare responses to BRs both in light and darkness. As our RoboFish is accepted as conspecific by both used populations of the Atlantic molly only under light conditions but not in darkness, we argue that our replica is providing mostly visual cues.